2006
DOI: 10.1002/jcb.20866
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoclastogenesis by gap junction communication

Abstract: Receptor activator of NF-kappaB ligand (RANKL) is crucial in osteoclastogenesis but signaling events involved in osteoclast differentiation are far from complete and other signals may play a role in osteoclastogenesis. A more direct pathway for cellular crosstalk is provided by gap junction intercellular channel, which allows adjacent cells to exchange second messengers, ions, and cellular metabolites. Here we have investigated the role of gap junction communication in osteoclastogenesis in mouse bone marrow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…Our assessment of functional GJIC in HOS cells done by DEPArrayª microfluidic approach is in agreement with a recent new high throughput screening proposed by Lee et al (2015) between the two cell types during this crucial phase (Pollmann et al, 2005, Saito-Katsuragi et al 2007). In line with several studies (Gramsch et al 2001, Matemba et al 2006, we found an increase in Cx43 expression in the differentiated osteoblasts. This may explain why we observed GJIC between hOS cells and differentiated osteoblasts at either 7 or 21 days, whereas no cell-cell communication was observed between osteoblast precursors (MSC) and tumour cells.…”
Section: Osteosarcoma Cells Transduced Withsupporting
confidence: 93%
See 1 more Smart Citation
“…Our assessment of functional GJIC in HOS cells done by DEPArrayª microfluidic approach is in agreement with a recent new high throughput screening proposed by Lee et al (2015) between the two cell types during this crucial phase (Pollmann et al, 2005, Saito-Katsuragi et al 2007). In line with several studies (Gramsch et al 2001, Matemba et al 2006, we found an increase in Cx43 expression in the differentiated osteoblasts. This may explain why we observed GJIC between hOS cells and differentiated osteoblasts at either 7 or 21 days, whereas no cell-cell communication was observed between osteoblast precursors (MSC) and tumour cells.…”
Section: Osteosarcoma Cells Transduced Withsupporting
confidence: 93%
“…In addition, it is well-known that the formation of Gap junctions is necessary for the maturation process of osteoblasts (Lloyd and Donahue, 2010). In addition, it has previously been demonstrated that human precursors and mature osteoclasts express Cx43, which appears to be related to osteoclastogenesis (Matemba et al, 2006, Schilling et al, 2008, Stains and Civitella, 2016. One crucial question is now to determine whether or not osteoclasts/osteoblasts are able to communicate together using GJIC.…”
Section: Osteosarcoma Cells Transduced Withmentioning
confidence: 99%
“…These experimental evidences suggest that GJIC is crucial for osteoclast formation and survival. Recently, the gap junction inhibitor carbenoxolone was shown to significantly inhibit osteoclastogenesis stimulated by PTH, prostaglandin E 2 (PGE 2 ) and 1,25(OH) 2 D 3 in mouse bone marrow cultures (70), further implicating the role of GJIC in conveying the stimulating signals of these hormones on osteoclast formation and bone remodeling.…”
Section: Gap Junctions In Osteoclast Formationmentioning
confidence: 99%
“…Cx43 is contained in bone-resorbing osteoclasts, and is involved in regulating the size and multi-nuclearity of human osteoclasts. 20,21 Several studies have shown that osteoclast fusion is associated with the upregulation of Cx43 expression in bone marrow cultures, and that a gap-junction inhibitor dramatically inhibited bone resorption, which caused a decrease in the number and activity of osteoclasts. 22,23 We have also reported that treatment with siRNA targeting rat Cx43 reduced the number of osteoclastlike cells in areas of pannus invasion into the joints of CIA rats.…”
Section: Discussionmentioning
confidence: 99%